Hydrogeochemical behavior of the Barreiras aquifer in the metropolitan region of Belém, state of Pará - Cabral, Natalina Maria Tinôco; Lima, Lilianne Maia (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Between June 2000 and March 2002, nine campaigns of water sampling were carried out in residential wells of 3 quarters of Belém, Pará, Brazil. In order to have a better knowledge about the hydrogeochemistry behavior of representative water samples, several chemical parameters were statistically treated. The results show that the studied waters are differentiated if compared to other waters in a regional scale. The main parameters that marked this differentiation included the electric conductivity, contents of chloride, sodium, ammonium, and nitrate, and pH. It is stood out that joined ammonium and nitrate concentrations are above or next to the limit to effective potability and that such parameters are the main markers of water contamination through servants of domestic effluent. Nitrate has positive correlation with electric conductivity and weak positive correlation with chloride, sodium and calcium. Ammonium has shown positive correlation with chloride and negative correlation with calcium. This study permitted to indicate that, in the studied waters, the electric conductivity and the behavior of chloride and calcium are good markers for contamination through servants of domestic effluent. The factor analyses are consistent with the observed correlations.
Keywords: Barreiras aquifer; Hydrogeochemical; Septic systems; Belem; Pará